2015
DOI: 10.1016/j.procs.2015.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Approaches for System of Systems: Events-based versus Agent Based Modeling

Abstract: In order to understand how we may engineer system of systems (SoS), we will have to rely significantly on our abilities in modeling and simulation. While there are some models of non-specific SoS, few attempts have been made to demonstrate these models with simulation. Simulations of SoS are usually specific cases. Likewise, in the description of a SoS, most of the approaches have focused on their characterization, yet this characterization has not been greatly utilized as an underlying feature in the modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…M&S enable visualization of SoS dynamics [17,[22][23][24][25]. Several application domains adopt M&S [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…M&S enable visualization of SoS dynamics [17,[22][23][24][25]. Several application domains adopt M&S [17].…”
Section: Introductionmentioning
confidence: 99%
“…Baldwin et al summarize current techniques found in the literature to simulate SoS [24]. Event-based modeling is the most prominent approach, as researchers can program different states a system undergoes to comprehend the behavior of the SoS as a whole [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions in lower domains are clarified [Erden et al, 2008] Mathematical systems theory Multidimensional feedback systems which can either be continuous, sampled (temporal discrete) and discrete event Understanding feedback operations in systems [Maier and Rechtin, 2000] [Maier and Rechtin, 2000]. Identify emergent behavior [Baldwin et al, 2015] Public choice and behavior models Models of human behavior and decision making Understanding the human system [Maier and Rechtin, 2000] Considering the threads and scenario type, especially scenarios are useful tools to envisage future usage scenarios and contexts for the system [Ionita, 2005]. More recently, [Curry and Ross, 2015] discuss extensions to the Epoch-Era Analysis framework.…”
Section: Behavioral Modelsmentioning
confidence: 99%
“…This often allows modeling of emergent behavior. This is especially useful when modeling Systems of Systems [Baldwin et al, 2015].…”
Section: Behavioral Modelsmentioning
confidence: 99%